Care of adolescents sheltered in maternity hospitals from the perspective of health professionals - Penna,Lucia Helena Garcia (2012)
OBJECTIVE: Discuss determinant aspects of quality care of pregnant adolescents sheltered in a maternity hospital, according to the perspective of health professionals. METHODS: Study with a qualitative, exploratory approach, conducted in a maternity hospital in the Municipality of Rio de Janeiro - RJ, reference for sheltered youngsters. The subjects of the study were 14 health professionals. The data were treated according to the Content Analysis technique. RESULTS: Two categories of analysis emerged: Characteristics of care provided by health professionals at the maternity hospital directed towards the sheltered adolescent mother and her child; Characteristics of the organization/structure of the maternity hospital that affected the care of the sheltered pregnant adolescents. CONCLUSION: It is necessary to incorporate the guiding practices of integrality/interdisciplinarity into the service. The stigmatization of these youngsters is one of the greatest challenges to full assistance and care. The maternity hospital space is a rich environment for the nurse-adolescent dialogic process.